PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI KSPPS KARIMA UTAMA SYARIAH KARANGANYAR - Editya, Editya; Aji, Ambyah Atas (Surakarta Management Journal, 2022)
This study aims to determine the effect of leadership style and work discipline on the performance of KSPPS Karima Utama Syariah Karanganyar employees either partially or simultaneously. The hypothesis in this study is that leadership style and work discipline affect the performance of KSPPS Karima Utama Syariah Karanganyar employees both partially and simultaneously. This research is a quantitative case study with a survey method. Primary data obtained from the answers to the questionnaire. The research population was 36 employees and the sample in this study was taken using the census technique, so the number of samples in this study was 36 respondents. The analysis technique used is multiple linear regression test, F test, t test, and coefficient of determination test. The results showed that leadership style and work discipline had an effect on the performance of KSPPS Karima Utama Syariah Karanganyar employees both partially and simultaneously